Newman's Error Analysis of Integer Material in Mts Al-Ihsan Medan Students - Della Permata Rahmah; Zul Amry (Jurnal Ilmiah Pendidikan Holistik (JIPH), 2022)
This study aims to determine the types of student errors, the factors that cause student errors in solving math problems based on the Newman procedure at MTs Al-Ihsan Medan and efforts to minimize student errors based on the Newman procedure. This type of research is descriptive qualitative. The subjects in this study were class VII students of MTs Al-Ihsan Medan, totaling 3 students, each of which was taken 1 student in the high category, 1 student in the medium category, and 1 student in the low category. Data collection techniques using written tests and interviews. Data analysis was carried out with the data reduction stage, the data presentation stage and the conclusion drawing stage. The results showed that the percentage of errors made by students in solving math problems related to integer material based on the Newman procedure were: (a) the percentage of reading errors was 20%, (b) the percentage of understanding errors was 84%, (c) the percentage of transformation errors was 72%. , (d) the percentage of error in processing skills is 54.66, and (e) the percentage of errors in writing the final answer is 80%.